Incidence trends of invasive and in situ breast cancer among females in Poland during 1999–2014 - Macek, Paweł; Hashim, Dana; Mańczuk, Marta; Błaszkiewicz, Ewa; Sosnowska-Pasiarska, Barbara; Biskup, Małgorzata; Król, Halina; Smok-Kalwat, Jolanta; Góźdź, Stanisław (Medical Studies/Studia Medyczne, 2017)
Introduction : Breast cancer is the most common malignant tumour among females worldwide, including low and middle-income countries. It affects 25% of the female population and yearly is diagnosed in 1.5 million women. Aim of the research : To determine the trends and distributions for invasive and in situ breast cancer incidence rates between 1999 and 2014 in Poland overall and in the voivodeships with the greatest proportion of females aged ≥ 65 years old. Material and methods : Data for 226,146 invasive (C50) and 7865 in situ (D05) breast cancer incidence (1999–2014) for all females was obtained from published data of the Polish National Cancer Registry (NCR). Age-standardised rates (ASRs) per 10 5 person-years for all ages of combined females with 95% confidence intervals (CI) were calculated. Joinpoint regression was performed to identify log-linear trends in both invasive and carcinoma in situ incidence rates in the analysed voivodeships and in Poland overall. Results : The ASRs of both invasive and in situ breast cancers showed increasing trends over the 1999–2014 period, with different patterns between analysed voivodeships. On average, average annual percent changes (AAPCs) varied from 1.6% to 7.9% annually, while in the Świętokrzyskie Voivodeship AAPCs remained below 0.9% annually. Conclusions : in situ and invasive breast cancer ASRs in Poland increased between 1999 and 2014. The Annual Percentage Change have slowed since 2004 in the analysed voivodeships, but not in Poland overall. It remains uncertain if breast cancer incidence rates will continue to increase or stabilise over time.